Ventilation history of Nordic Seas overflows during the last (de)glacial period revealed by species-specific benthic foraminiferal 14C dates - Mohamed, Ezat M.; Rasmussen, Tine L.; Thornalley, David J.R.; Olsen, Jesper; Skinner, Luke C.; Hönisch, Bärbel; Groeneveld, Jeroen (Paleoceanography, 2017)
Formation of deep water in the high‐latitude North Atlantic is important for the global meridional ocean circulation, and its variability in the past may have played an important role in regional and global climate change. Here we study ocean circulation associated with the last (de)glacial period, using water‐column radiocarbon age reconstructions in the Faroe‐Shetland Channel, southeastern Norwegian Sea, and from the Iceland Basin, central North Atlantic. The presence of tephra layer Faroe Marine Ash Zone II, dated to ~26.7 ka, enables us to determine that the middepth (1179 m water depth) and shallow subsurface reservoir ages were ~1500 and 1100 14C years, respectively, older during the late glacial period compared to modern, suggesting substantial suppression of the overturning circulation in the Nordic Seas. During the late Last Glacial Maximum and the onset of deglaciation (~20–18 ka), Nordic Seas overflow was weak but active. During the early deglaciation (~17.5–14.5 ka), our data reveal large differences between 14C ventilation ages that are derived from dating different benthic foraminiferal species:Pyrgo and other miliolid species yield ventilation ages >6000 14C years, while all other species reveal ventilation ages <2000 14C years. These data either suggest subcentennial, regional, circulation changes or that miliolid‐based 14C ages are biased due to taphonomic or vital processes. Implications of each interpretation are discussed. Regardless of this “enigma,” the onset of the Bølling‐Allerød interstadial (14.5 ka) is clearly marked by an increase in middepth Nordic Seas ventilation and the renewal of a stronger overflow.